PENGARUH KEPUASAN KONSUMEN DAN KUALITAS PRODUK TERHADAP KEPERCAYAAN KONSUMEN DI PT CITRA SUBLINDO ADITAMA - kwok, vivian; Daris Purba, S.E.I, M.S.I. (SCIENTIA JOURNAL, 2022)
In running a business that is very important and needed for companies, namely consumers. Because with the presence of consumers, activities can also run, but these will last longer if they can be matched and matched by the regional desires of telebut consumers. Companies that are able to maintain customer satisfaction and product quality are very profitable in the competition between companies. The purpose of this research is to know The Effect of Consumer Satisfaction and Product Quality on Consumer Trust in PT Citra Sublindo Aditama. The population and samples used in this research are consumers from PT Citra Sublindo Aditama, totaling 150 people. The sampling technique used was saturated sampling technique. Data collection techniques were carried out by distributing questionnaires or quantitative methods which then the results obtained by respondents through SPSS software version 25. The data analysis method used was multiple linear regression analysis. The results of this study show that 1) There is a significant to positive effect between consumer satisfaction on consumer trust, 2) There is a significant to positive effect between product quality on consumer trust and 3) There is a significant to positive effect between consumer satisfaction and product quality against consumer trust